2021
DOI: 10.7554/elife.59300
|View full text |Cite
|
Sign up to set email alerts
|

Microsecond interaural time difference discrimination restored by cochlear implants after neonatal deafness

Abstract: Spatial hearing in cochlear implant (CI) patients remains a major challenge, with many early deaf users reported to have no measurable sensitivity to interaural time differences (ITDs). Deprivation of binaural experience during an early critical period is often hypothesized to be the cause of this shortcoming. However, we show that neonatally deafened (ND) rats provided with precisely synchronized CI stimulation in adulthood can be trained to lateralize ITDs with essentially normal behavioral thresholds near 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 94 publications
2
25
1
Order By: Relevance
“…Previous studies on bilateral CI users with prelingual or early onset deafness suggest an important role of early auditory input in the establishment of ITD sensitivity ( Litovsky et al, 2010 , 2012 ; Salloum et al, 2010 ). Patients with early auditory deprivation showed no measurable sensitivity to ITDs on the lateralization task, whereas recent studies in rats have shown a comparable behavioral ITD sensitivity between animals with NH and those who were ND and received bilateral CIs ( K. Li et al, 2019 ; Rosskothen-Kuhl et al, 2021 ). It should be noted that Rosskothen-Kuhl and colleagues, fully inserted the animal electrode array into the middle turn through a cochleostomy and not into the basal turn via the round window, as performed in human studies.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies on bilateral CI users with prelingual or early onset deafness suggest an important role of early auditory input in the establishment of ITD sensitivity ( Litovsky et al, 2010 , 2012 ; Salloum et al, 2010 ). Patients with early auditory deprivation showed no measurable sensitivity to ITDs on the lateralization task, whereas recent studies in rats have shown a comparable behavioral ITD sensitivity between animals with NH and those who were ND and received bilateral CIs ( K. Li et al, 2019 ; Rosskothen-Kuhl et al, 2021 ). It should be noted that Rosskothen-Kuhl and colleagues, fully inserted the animal electrode array into the middle turn through a cochleostomy and not into the basal turn via the round window, as performed in human studies.…”
Section: Discussionmentioning
confidence: 81%
“…Another notable conclusion of the model's prediction about improved resolution at small ITDs is that it potentially provides a mechanistic explanation for the recent reports of highly precise ITD sensitivity both on the level of midbrain coding (Buck et al, 2021) and perceptual resolution (Rosskothen-Kuhl et al, 2021) in bilaterally implanted rats. Since these animals have smaller inter-ear-distances compared to human subjects, the predicted region of increased LSO ITD coding capacity would 10.3389/fnins.2022.1021541 cover a large fraction of the available ITDs in rats, and hence provide an advantageous effect on spatial resolution for almost the entire frontal field.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, three studies in rats have shown a similar sensitivity in tuning between animals with NH and those who were early-deafened and received CI stimulation [ 95 97 ]. Supportive of their assertion that tuning was similar, many neurons recorded from the inferior colliculus in these rats were significantly tuned to ITDs, in contrast to previous studies with rabbits [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments in rabbits support the idea that consistent BiCI stimulation can restore ITD sensitivity [ 98 ]. It should be noted that because few animals participated in the study by Rosskothen-Kuhl and colleagues, the lack of effect (i.e., no significant difference in ITD tuning between NH and late-implanted groups) in one study could have been driven by the variability in rats with NH [ 95 ].…”
Section: Discussionmentioning
confidence: 99%